The Relationship Between Specific and Sensitive Nutrition Interventions and the Incidence of Stunting in Toddlers - Andiani Andiani; Tutik Lestari; Nani Supriyatni; Tati Sumiati (BIOSAINSTEK, 2025)
Stunting, or below-standard height, is a nutritional problem commonly found in developing countries. Stunting negatively impacts growth, development, and productivity. It can increase the risk of infectious diseases, chronic diseases, and death, which will subsequently reduce work productivity in adulthood. Children who cannot catch up on growth later on can cause bigger problems, and in the future, Indonesia may experience a lost generation. Method: This study uses a descriptive-analytical method with a cross-sectional research design. The population consisted of all mothers with toddlers aged 0-59 months in 2021, totaling 520 toddlers, while the sample included 99 mothers of toddlers. Data collection on toddlers was conducted by measuring body length/height with a microtoise BB to determine stunting status and using a questionnaire. The research results were analyzed univariately and bivariately using the Chi-Square test. Results: Specific nutrition interventions, when viewed from the PMT variable (0.035), IMD counseling and exclusive breastfeeding (0.001), vitamin A capsule administration (0.022), and immunization (0.036), are related to the incidence of stunting in toddlers. Meanwhile, sensitive nutrition interventions, when viewed from the information variable (0.030) about stunting, are related to the incidence of stunting in toddlers. Conclusion: Preventing stunting requires appropriate handling through both specific and sensitive nutritional interventions together. The research results indicate that there are 5 variables related to the occurrence of stunting in toddlers, including PMT, IMD counseling and exclusive breastfeeding, administration of vitamin A capsules, immunization, and provision of information about stunting.